PENGARUH ENVIRONMENTAL DAN SOCIAL SUSTAINABILITY DISCLOSURE TERHADAP FIRM PERFORMANCE - Hartaniya Araya (2023)
This research is a quantitative study with the aim of empirically proving the effect of environmental disclosure and social sustainability disclosure on firm performance seen through the aspects of return on assets and return on equity. This research uses secondary data obtained from annual reports and sustainability reports of non-financial companies on the Indonesia Stock Exchange (IDX) for 2019-2021. The sample in this study was 171 and data testing used the STATA version 13 application. The results showed that (1) environmental disclosure had a positive and significant effect on return on assets but had no positive effect on Return On Equity, (2) corporate social sustainability disclosure has no effect on return on assets, but has a positive effect on return on equity (3) Financial leverage, firm size and capital intensity have a positive effect can control the return on assets and return on equity variables.